"Like a Dream, an Illusion, a Drop of Dew, a Flash of Lightning": Buddhist (Un)reality, Thought Experiments, and the "Ecological Dharma Eye" in Lu Yang's Material World Knight Game Film. Issue 1 (1st June 2022) - Monnet, Livia
Abstract: This article argues that the conceptualization of the (un)reality of the phenomenal or material world ( qishijie ) in Lu Yang's animated short Material World Knight Game Film ( MWKGF, 2020) at once follows and departs significantly from the Theravada and Mahayana traditions it references. MWKGF' s reconfiguring of Buddhist notions of (un)reality is especially apparent in its representation of samsara (cycle of birth and rebirth) and in its questioning of Buddhist wisdom through the lens of neuroscience, psychotherapy, and (popular versions) of quantum theory. The film further suggests that Buddhist philosophy can be effectively expounded and played, as an "executable thought experiment" in/as a video game. The article shows in conclusion that MWKGF also envisions an "ecological dharma eye manifesto" that seems to call for an epistemic-technoscientific-spiritual revolution.